(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Batasan Hills Quezon City reportedly has a high crime rate in 2023. The majority of the people living in Batasan Hills are concerned about their safety. The crimes included are eight index crimes; murder, homicide, physical injury, rape, robbery, theft, and motorcycle theft. According to the QCPD, the high crime solution rate can be attributed to three things: the full use of QCitizen Helpline 122, an improved emergency hotline that offers assistance in times of need as well as a mechanism for callers to complain and provide feedback; the effectiveness of the three-minute police response time policy through the Integrated Command and Control Center; and the ongoing conduct of simulation exercises and constant monitoring of identified crime-pr. The data gathered showed that the respondents are characterized by age, gender, and civil status, and all of the respondents were police personnel who are working in Police Station 6 Batasan Hills Quezon City. The data gathered shows that the police personnel are responsive when needed. The police officers/personnel are also in favor of additional mobile cars to improve the response of police to take action in emergency situations. The respondents are also in favor of adding police patrol officers. The result of the study shows that most of the police personnel that were surveyed are men. Police officers/personnel are responsive in order to prevent or lessen the crime in a certain place. The impact of responsiveness and alertness of the police personnel can lower the crime rate in Quezon city.